Introduction: Modernism and/as Pedagogy. Issue 3 (August 2019) - Howarth, Peter
Abstract : Literary modernism co-developed with modern pedagogy, particularly progressive education's pedagogy of experience. But although many modernists were teachers, the deep relationship between the writer and the classroom has not had the critical attention it deserves. Since the 1970s, progressivism has been caricatured as an individualist affirmation of the given self at the expense of learning from tradition. But its real roots, like much of modernism's, lie in the process ontologies of Bergson, James and Dewey, which essay an interactive, environment-dependent account of persons as developing systems. During the 1920s and 30s, both modernist experiments in narrative and progressive experiments in the classroom let characters, selves and meanings emerge from their environmental situations. Both drew attention to the processes of the mind in formation, to the way language mediates the self to itself, and to the unfinished nature of all understanding. 'Education', remarked Dewey, 'must be considered as a continuing reconstruction of experience', and the same is true for the reader of modernism, who is continually faced with the gap between experience in the happening and the words to make sense of it.